8 Stat. at Large of Pa. 410-12, ch. 705, § 1 (1902) - (:unkn) unknown (My University, 1774)
Restricted the firing of handgun, pistol, or other firearms, as well as squibs, rockets, or other fireworks on New Years Eve or the two days following. Violators fined ten shillings.
Keywords: DISCHARGE